2014
DOI: 10.1055/s-0034-1377034
|View full text |Cite
|
Sign up to set email alerts
|

Informationsbedarf zur medizinischen Rehabilitation der Deutschen Rentenversicherung – Ergebnisse eines Online-Surveys mit niedergelassenen Ärzten

Abstract: General practitioners have high information needs regarding different aspects of rehabilitation which are not satisfied with existing sources of information. The development of a user-friendly website with comprehensible information on the required aspects seems necessary to increase the acceptance and understanding of medical rehabilitation among practitioners and therefore to optimise rehabilitation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 8 publications
0
13
0
18
Order By: Relevance
“…Moreover, users can easily access them. They also correspond to user expectations and preferences since clinicians themselves favor web-based information on rehabilitation-related contents [21]. As noted above, however, these tools are still uncommon in rehabilitation, especially with respect to work-related programs and are rarely accompanied by evaluation research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, users can easily access them. They also correspond to user expectations and preferences since clinicians themselves favor web-based information on rehabilitation-related contents [21]. As noted above, however, these tools are still uncommon in rehabilitation, especially with respect to work-related programs and are rarely accompanied by evaluation research.…”
Section: Discussionmentioning
confidence: 99%
“…It is a low-threshold tool that is easy to adapt and can be accessed by a large number of users. A German study with general practitioners showed that physicians rate this format favorably [21]. However, online tools that support this implementation are largely lacking in rehabilitation, especially with respect to work-related programs.…”
Section: Introductionmentioning
confidence: 99%
“…In einem ersten Schritt wurde vor der Fortbildung bei den Teilnehmern der reha-spezifische Informationsbedarf mit dem Fragebogen einer Vorgängerstudie erfasst [14]. Dieser wurde in einem Online-Survey bei niedergelassenen Ärzten eingesetzt, um deren rehabilitationsbezogenen Informationsbedürfnisse zu erfassen.…”
Section: Fragebogenerhebungunclassified
“…Bisher vorliegende Informationen zur medizinischen Rehabilitation werden von niedergelassenen Ärzten als schwer verständlich und wenig hilfreich empfunden und dementsprechend nicht genutzt [12,13,14]. Insbesondere die Website der DRV Bund, die eine Fülle an Informationen zur medizinischen Rehabilitation bereit stellt, wird nur in geringem Umfang genutzt, da sie zum einen nicht bekannt ist und zum anderen den Bedürfnissen der niedergelassenen Ärzte nicht entspricht.…”
Section: Introductionunclassified
See 1 more Smart Citation